Women in the Frankincense Value Chain: A Review of Customary Law and Gender Equality in Tapanuli - Muhammad Ikhsan Lubis; Asti Inayah; Salman Paris Harahap; Bahar Elfudllatsani; Adhita Pradana (Gloria Justitia, 2026)
Frankincense is not only an economic commodity but also a cultural entity governed by a strong customary law system in the communities that produce it, such as Tapanuli. In a customary law system that is often patriarchal, the position of women requires deeper examination. This study stems from a contradictory portrait: on one hand, women are actively involved in the frankincense value chain, yet on the other hand, their contributions are often unrecorded and marginalized, and they lack legal recognition and economic compensation. This study used a qualitative approach with a case study method in North Tapanuli. Data were collected through in-depth interviews with key informants (women artisans, customary elders, and female community leaders), participatory observation of the incense processing process, and a study of documents related to local customary rules. Data were analyzed interactively through data reduction, data presentation, and conclusion drawing techniques. The research findings show that women play a central and critical role in the post-harvest and processing stages, which determine the quality and market value of the incense. However, prevailing customary laws tend to position women in the domestic sphere and deny them access to strategic decision-making, tree ownership, and fair distribution of economic benefits. Their contributions are often categorized as 'assistance' or 'domestic obligations' rather than as economically valuable 'work' and thus are not valued equally with men's contributions. There is a significant gap between women's actual economic contributions to the Frankincense value chain and the recognition and protection provided by customary law. To achieve gender justice and women's economic empowerment, a more inclusive reinterpretation or revitalization of customary law is needed, without eroding core cultural values.